Procédures pour l’estimation des taux de protection effectifs dans les matrices entrées-sorties - Decaluwe, Bernard; Lee, Y. (L'Actualité économique, 1984)
ABSTRACTThis short note presents a procedure to estimate effective rate of protection coefficient using an input-output approach. In the first section, the procedure to estimate nominal rate of protection on input and output will be quickly discussed. The section 2 points out two options in treating indirect taxes on output. Finally, in the last two sections, a procedure to decompose non tradeable sectors into tradeable parts and value added parts will be discussed.